Immunohistochemical analysis of the oxidative phosphorylation complexes in skeletal muscle from patients with mitochondrial DNA encoded tRNA gene defects. Issue 2 (29th January 2009) - De Paepe, B; Smet, J; Lammens, M; Seneca, S; Martin, J-J; De Bleecker, J; De Meirleir, L; Lissens, W; Van Coster, R
Abstract : Background: Mitochondrial diseases display a heterogeneous spectrum of clinical phenotypes and therefore the identification of the underlying gene defect is often a difficult task. Aims: To develop an immunohistochemical approach to stain skeletal muscle for the five multi-protein complexes that organise the oxidative phosphorylation (OXPHOS) in order to improve the diagnostic workup of mitochondrial defects. Methods: OXPHOS complexes were visualised in skeletal muscle tissue using antibodies directed against different subunits. The staining patterns of patients with heteroplasmic defects in mtDNA tRNA genes were compared with those of normal and disease controls. Results: Normal skeletal muscle displayed a checkerboard staining pattern for complexes I to V due to the higher mitochondrial content of slow muscle fibres versus fast fibres. In patients with tRNA defects, a much more heterogeneous staining pattern was observed for complex I (all six patients) and complex IV (4 of 6 patients): a mosaic staining pattern in which individual fibres displayed staining intensities that ranged from strong to negative. Ragged red fibres (RRFs) in patients with MERRF (myoclonic epilepsy and ragged red fibres) were all complex I and IV negative, while in patient with MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes) the majority of RRFs were complex I negative and complex IV positive. Conclusion: Immunohistochemical detection of OXPHOS complexes could represent a valuable additional diagnostic tool for the evaluation of mitochondrial cytopathy. The technique helps to detect heteroplasmic mtDNA defects. Staining for complex I in particular was able to identify two tRNA patients that stayed undetected with routine histochemical evaluation.